The elusive justice for women: a critical analysis of rape law and practice in Kenya - Lekakeny, Ruth Nekura (Department of Public Law, 2015)
This thesis seeks to uncover the challenges encountered by women and girl victims of rape in seeking recourse through the criminal justice system in Kenya. To do this I focus on their experiences in three major points of service provision, i.e. the police, the health facilities and the courts. I then explore, as a secondary research question, whether an integrated service provision approach provides solutions to these challenges. Article 48 of the Constitution of Kenya provides that 'The state shall ensure access to justice for all persons and, if any fee is required, it shall be reasonable and shall not impede access to justice'27 This obligation places a tall order on the state and all its agents to ensure that anyone in pursuit of justice should access it with the minimum obstacles.